Eksplorasi Perbedaan dan Interaksi Immersion dan Flow dalam Virtual Run Event [Exploration of the Differences and Interactions Between Immersion and Flow in Virtual Event Runs] - Kiesa, Celine; Nathanael, Nevio; Saragih, Harriman Samuel; Jayawardhana, Irman (Milestone: Journal of Strategic Management, 2021)
This study aims to explore the differences between flow and immersion experiences and find the relationship between individual flow and immersion experiences in virtual run events. This research is qualitative research that uses narrative methods towards individuals by using interview for collecting information. The target of this study is the virtual run event participants from the period May–June 2021. This study involves informants who are sought through social media and personal relationships of the researchers. The search for informants was assisted by snowball sampling to be able to find informants who met the criteria. The results of this study found differences between flow and immersion and also the interaction between flow and immersion.BAHASA INDONESIA ABSTRAKPenelitian ini bertujuan untuk mengeksplorasi perbedaan pengalaman flow dan immersion dan juga mencari keterkaitan antara pengalaman flow dan immersion individu dalam virtual run event. Penelitian ini merupakan penelitian kualitatif yang menggunakan metode riset naratif terhadap individunya dengan menggunakan teknik wawancara dalam menggali informasinya. Target dari studi ini adalah peserta virtual run event dari periode Mei–Juni 2021. Studi ini melibatkan informan yang dicari melalui media sosial dan relasi pribadi dari peneliti. Pencarian informan dibantu dengan snowball sampling untuk dapat menemukan informan yang memenuhi kriteria. Dari hasil studi ini ditemukan perbedaan antara flow dan immersion dan juga interaksi antara flow dan immersion.